(untitled) (Studia Prawnicze / The Legal Studies, 1997)
"Widoki na utrzymanie pożycia małżeńskiego" [stanowiące przesłankę zawieszenia postępowania na podstawie art. 440 k.p.c.] to nic innego jak przypuszczenie sądu, że rozkład pożycia jeszcze nie nastąpił. Sugerowanie, że konieczne jest prowadzenie postępowania dowodowego i wyznaczanie w tym celu rozprawy, aby ustalić istnienie podstawy do zawieszenia postępowania w trybie art. 440 k.p.c., jest nieporozumieniem. Przepis ten powinien być zastosowany wówczas, kiedy próby pojednania małżonków nie dały rezultatu, ale sąd - na podstawie zachowania się stron, czasami nawet gestów czy uśmiechu przypominającego uśmiech skłóconych dzieci - może nabrać przekonania, że "istnieją widoki na utrzymanie pożycia małżeńskiego". W takiej sytuacji, aby nie pogłębiać konfliktu prowadzeniem postępowania dowodowego, zwłaszcza polegającego na przesłuchiwaniu świadków, sąd zawiesza je na takim etapie procesu, na jakim to przekonanie sądu powstało. Może to być posiedzenie pojednawcze, rozprawa lub posiedzenie niejawne zainicjowane pismem procesowym jednej lub obydwu stron. “The prospect of the maintenance of conjugal life” [which is a prerequisite for suspending the proceedings under Article 440 of the Code of Civil Procedure] is nothing more than a presumption by the court that the breakdown of conjugal life has not yet occurred. To suggest that it is necessary to hold a hearing of evidence and to set a hearing for that purpose in order to establish the existence of grounds for suspending of proceedings under Article 440 of the Code of Civil Procedure is a misunderstanding. This provision should be applied when attempts at reconciliation between the spouses have failed, but the court – on the basis of the parties’ behaviour, sometimes even gestures or smiles reminiscent of those of quarrelling children – may become convinced that “there are prospects for the maintenance of conjugal life”. In such a situation, in order not to aggravate the conflict by conducting the hearing of evidence, especially those involving the hearing of witnesses, the court shall suspend them at such a stage of the proceedings at which the court’s conviction has arisen. This may be a conciliatory hearing, a hearing or a closed hearing initiated by a pleading of one or both parties.